2020
DOI: 10.1039/c9py01915d
|View full text |Cite
|
Sign up to set email alerts
|

Order–disorder transition in supramolecular polymer combs/brushes with polymeric side chains

Abstract: Supramolecular polymer combs/brushes can be used as smart materials which incorporate the properties of linear polymers with branch polymers depending on the temperature, grafting density, branch molecular weight and most importantly type of non-covalent interaction between the main chain and side chains. Three sets of polymers were synthesized and mixed based on a specific interaction between the main chain and the side chain polymers. The first two sets based on the combination of 2,4-diamino-1,3,5-triazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Indeed, as mentioned in Section , a lamellar periodicity of around 100 Å implies that the HPB chains located between two lamellae are oriented, especially in the vicinity of the lamellae where the segments are strongly stretched and impenetrable. As discussed in refs and , this also contributes to the sample rigidity.…”
Section: Results and Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, as mentioned in Section , a lamellar periodicity of around 100 Å implies that the HPB chains located between two lamellae are oriented, especially in the vicinity of the lamellae where the segments are strongly stretched and impenetrable. As discussed in refs and , this also contributes to the sample rigidity.…”
Section: Results and Discussionmentioning
confidence: 79%
“…9,60,61 If the supramolecular junctions organize into well-defined stacks, it has been shown that supramolecular polymer brushes can be obtained, with either lamellar or hexagonal cylinder morphologies, depending on the aggregation strength as well as on the mobility of the pending chains. 10,62 The examples described above support that it is possible to obtain a strong reversible network based on the short linear building blocks bearing directional binding motifs at their extremities. This requires the phase separation, aggregation, glass formation, or crystallization of the supramolecular junctions, 24 which strongly affect the sample properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are only a few reports of UPy monomer polymerization with RAFT, ,, we checked the linearity of the polymerization kinetics during the process. UPy-functionalized CTAs have already been shown to maintain the linear growth of RAFT polymers and thus a methacrylated version was expected to perform similarly.…”
Section: Resultsmentioning
confidence: 99%
“…55 Therefore, ODINs are more likely to make hydrogen bonding with PEG (or PTHF) 41 than with PmA or PnBa in our latest study. 56,57 This leads to an easier dissociation of the dimerized ODIN moieties in the PEG matrix in comparison to PmA, and consequently, PEG-ODINs can flow faster at higher temperatures or longer frequencies. In other words, the brush morphology is easier to be obtained in PmA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%